ABILITY TO MILL ROCKS IN OPEN-PIT MINING - Bołoz, Łukasz; Krauze, Krzysztof (International Multidisciplinary Scientific GeoConference SGEM, 2018)
The article discusses various methods of rock mining used in open-pit mining.The used machines were presented and attention was paid to the scope of their application and the limitations that they are subject to when mining various types of minerals. Then, the author's method for determining resistance to the mining of undisturbed soil was presented along with an example of application. On the basis of studies on the properties of the undisturbed soil carried out in one of the Polish open-pit mines, the technical abilities of mechanical mining of rocks were discussed. In particular, attention was paid to the selection of the optimal method of mechanical mining. A technical solution in form of a bulldozer adapter has been considered. In chose cases, it allows to replace the use of extracting with explosive material or breaking off. At the same time, an adaptation of the commercial solution of the TD-40 bulldozer to use milling as a method of exploiting the deposit in open-pit mining was presented. Taking into consideration the mine's minimum requirements concerning the machinery efficiency, values of geometric, kinematic and energy parameters of the mining adaptor have been proposed. As a result, an alternative method of rock mining in open-pit mining has been proposed, in this case for marl and chalk limestone mines. This solution is an economically advantageous substitute for expensive open-pit shearers.